Interplate versus intraplate strike-slip deformed belts: examples from SW Iberia - Romão, J. (2022)
A complete transition in tectonic style between pure thrust belts and pure strike-slip beltscan be envisaged, both in interplate and intraplate settings, by a combination of thrust and strike-slipcomponents of displacement. The accommodation of shortening components in strike-slip deforma-tion belts has been discussed recently on the basis of two alternative perspectives: (1) the “sub-horizon-tal attachment model”, where discrete strike-slip faulting of rigid blocks in the schiszosphere evolves tocontinuous movement in plastosphere through a bottom-up driving mechanism controlled by verticalcoupling across the lithosphere, and (2) the “accommodation model” that considers decoupling with-in a heterogeneous and anisotropic plastosphere. Two examples of variable shortening componentaccommodation in strike-slip deformation belts of the SW Iberia Variscides are reported and discussed.In the Tomar-Badajoz-Córdoba shear zone, an important shortening component is accommodated inflat-lying bends around the horizontal axis within a WNW-ESE flower-structure with sinistral strike-slip component; the geodynamic evolution points to an intraplate setting for this structure. In the N-S, Porto-Tomar-Ferreira do Alentejo, dextral shear zone, the shortening component is restricted torestraining bends around the vertical axis; the geodynamic evolution allows inferring a transformnature for this structure, thus indicating an interplate setting. For these examples, the “accommodationmodel” is preferred to the “sub-horizontal attachment model”